The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1292/jvms.12-0433
|View full text |Cite
|
Sign up to set email alerts
|

The Pathogenicity and Host Immune Response Associated with H5N1 Highly Pathogenic Avian Influenza Virus in Quail

Abstract: ABSTRACT. Quail, like chickens, are susceptible to H5N1 subtype highly pathogenic avian influenza virus (HPAIV). Both birds experience high mortality, but quail usually survive a few more days than chicken. To understand why, we monitored quail and chickens after inoculation with 10 6 fifty-percent egg infectious doses of HPAIV A/whooper swan/Aomori/1/2008 (H5N1). The clinical course initiated as depression at 48 hr post inoculation (h.p.i.) in quail and at 36 h.p.i. in chicken, and all infected birds died. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Gene expressions of inter‐leukin 6 (IL‐6), toll‐like receptor (TLR) 7 and interferon (IFN) α in each avian species and retinoic acid inducible (RIG‐I) in Muscovy ducks were assessed by qRT‐PCR. Primer sequences are described in (Cornelissen, Post, Peeters, Vervelde, & Rebel, ; Uno et al., ). Primers were diluted at 2.5 m m following manufacturer instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Gene expressions of inter‐leukin 6 (IL‐6), toll‐like receptor (TLR) 7 and interferon (IFN) α in each avian species and retinoic acid inducible (RIG‐I) in Muscovy ducks were assessed by qRT‐PCR. Primer sequences are described in (Cornelissen, Post, Peeters, Vervelde, & Rebel, ; Uno et al., ). Primers were diluted at 2.5 m m following manufacturer instructions.…”
Section: Methodsmentioning
confidence: 99%
“…A recent Cochrane review reported that antiviral therapies had little benefit for severe influenza patients [14, 15]. Furthermore, AI continues to require prolonged mechanical ventilation in the intensive care unit, and AI-associated mortality remains high at 30–50 % despite optimal supportive care [3, 16]. …”
Section: Introductionmentioning
confidence: 99%
“…The important pro-inflammatory cytokines IL-6 and TNF-α cause severe damage to the lungs during influenza infection [28] , and the overexpression of pro-inflammatory cytokines increases the pathogenicity of influenza virus [9,29] . Compared with the model group, the expression of IL-1α, IL-6, and TNF-α in lung tissue was decreased significantly after treatment with GGD and OP.…”
Section: Ggd Regulated the Expression Of Il-1α Il-6 And Tnf-αmentioning
confidence: 99%